Aelius Aristides between Greece, Rome, and the gods - Harris, William V. (William Vernon); Holmes, Brooke, 1976- (Columbia studies in the classical tradition, 2008)
Wealthy, conceited, hypochondriac (or perhaps just an invalid), obsessively religious, the orator Aelius Aristides (117 to about 180) is not the most attractive figure of his age, but because he is one of the best-known - and he is intimately known, thanks to his "Sacred Tales"--His works are a vital source for the cultural and religious and political history of Greece under the Roman Empire. The papers gathered here, the fruit of a conference held at Columbia in 2007, form the most intense study of Aristides and his context to have been published since the classic work of Charles B